2016
DOI: 10.1007/s00464-016-5258-2
|View full text |Cite
|
Sign up to set email alerts
|

Does peritoneal flap closure technique following transabdominal preperitoneal (TAPP) inguinal hernia repair make a difference in postoperative pain? A long-term quality of life comparison

Abstract: Tacked, sutured, and stapled techniques for peritoneal flap closure following TAPP have no significant differences in operative outcomes, postoperative quality of life, or resolution of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Ross et al [ 15 ] reported that suture closure of the peritoneum resulted in less early postoperative pain than tacked closure, and improved 2-wk postoperative activity compared with stapled and tacked closures. Subsequently, based on a larger sample size and a 2-yr follow-up, Ross et al [ 16 ] found that there were no significant differences between the tacked, sutured and stapled techniques. However, a prospective randomized study by Oguz et al [ 17 ] reported peritoneal closure using tacks increased short-term pain compared with suture closure.…”
Section: Discussionmentioning
confidence: 99%
“…Ross et al [ 15 ] reported that suture closure of the peritoneum resulted in less early postoperative pain than tacked closure, and improved 2-wk postoperative activity compared with stapled and tacked closures. Subsequently, based on a larger sample size and a 2-yr follow-up, Ross et al [ 16 ] found that there were no significant differences between the tacked, sutured and stapled techniques. However, a prospective randomized study by Oguz et al [ 17 ] reported peritoneal closure using tacks increased short-term pain compared with suture closure.…”
Section: Discussionmentioning
confidence: 99%
“…We just detailed the care that must be taken to fix the mesh with tacks, most commonly used method, and correlate with inverted Y and the five triangles. Atraumatic fixation of the mesh (glues or fibrin sealants and self-gripping meshes) has been advocated by many authors and be a good option to avoid complications specific related to tacks, especially chronic pain 18 , 19 , 20 . As well, it does not appear to be associated with an increased risk of recurrence and may be associated with a lower risk of chronic pain 20,21.…”
Section: Discussionmentioning
confidence: 99%
“…The final controversy raised by our paper is how the peritoneum in TAPP should be approximated. Although there is one paper that suggests tacking the peritoneum is safe 1,11 , we feel that this technique is risky. Blind placement of penetrating fixation of the peritoneum, whether permanent or absorbable may unnecessarily injure the ilioinguinal and iliohypogastric nerves and therefore should be avoided.…”
Section: Updatementioning
confidence: 98%